2014
DOI: 10.1128/aac.01332-13
|View full text |Cite
|
Sign up to set email alerts
|

Miltefosine Increases Lipid and Protein Dynamics in Leishmania amazonensis Membranes at Concentrations Similar to Those Needed for Cytotoxicity Activity

Abstract: b Miltefosine (MT) is a membrane-active alkylphospholipid licensed for the topical treatment of breast cancer skin metastases and the oral treatment of leishmaniasis, although its mechanism of action remains unclear. Electron paramagnetic resonance (EPR) spectroscopy of a spin-labeled lipid and a thiol-specific spin label in the plasma membrane of Leishmania promastigotes showed that MT causes dramatic increases in membrane dynamics. Although these alterations can be detected using a spin-labeled lipid, our ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 38 publications
3
32
0
3
Order By: Relevance
“…The IC 50 values of the sesquiterpene nerolidol and the monoterpenes (+)-limonene, α-terpineol and 1,8-cineole were 0.008, 0.549, 0.678 and 4.697 mM, respectively [16]. This result demonstrated that the in vitro cytotoxicity of nerolidol was similar to that of miltefosine, which is the first effective oral drug approved for the treatment of visceral and cutaneous leishmaniasis [32]. Overall, these IC 50 values and lysis results partially agree with the results obtained in this work.…”
Section: Discussionsupporting
confidence: 63%
“…The IC 50 values of the sesquiterpene nerolidol and the monoterpenes (+)-limonene, α-terpineol and 1,8-cineole were 0.008, 0.549, 0.678 and 4.697 mM, respectively [16]. This result demonstrated that the in vitro cytotoxicity of nerolidol was similar to that of miltefosine, which is the first effective oral drug approved for the treatment of visceral and cutaneous leishmaniasis [32]. Overall, these IC 50 values and lysis results partially agree with the results obtained in this work.…”
Section: Discussionsupporting
confidence: 63%
“…3B) indicated that only the 2×10 9 cells/mL concentration was sufficiently concentrated for an accurate calculation. At this cell concentration, the nerolidol IC 50 was 0.32×10 9 terpene molecules/cell, which was similar to that of miltefosine under the same experimental conditions [26]. To obtain the best fit of the IC 50 for nerolidol and (+)-limonene to the theoretical curves given by eqs.…”
Section: Discussionmentioning
confidence: 77%
“…Tea tree oil and its major active terpene component, terpinen-4-ol, demonstrated antiproliferative activity against two murine tumor cell lines, AE17 mesothelioma and B16 melanoma, with IC 50 values equal to or greater than 0.01% (∼588 µM), and they induced necrotic cell death and cell cycle arrest in both tumor cell lines [38]. Miltefosine is also able to increase membrane fluidity and induce cell lysis in L. amazonensis promastigotes at concentrations close to its IC 50 [26]. Interestingly, miltefosine has been shown to reduce the mitochondrial membrane potential and inhibit cytochrome c oxidase, changes that are linked to the apoptosis-like cell death [39].…”
Section: Discussionmentioning
confidence: 99%
“…Our data shows that T. brucei has limited tolerance for TbVAMP7B depletion, presumably due to impairment of endosomal-lysosomal fusion (45). Intriguingly, exposure to low concentration miltefosine complements the growth defect seen following TbVAMP7B depletion, suggesting that miltefosine treatment is able to promote vesicle membrane fusion in the endocytic system, a possible consequence of the enhanced membrane fluidity seen upon miltefosine exposure (60). TbVAMP7B has also recently been identified as a putative T. brucei apolipoprotein-L1 sensitivity determinant (61), and other workers have highlighted the importance of the intracellular transit of apoL1-carrying membrane to trypanolysis (62, 63).…”
Section: Discussionmentioning
confidence: 99%